Professionalism and Competence of Islamic Religious Education Teachers (Issues and Policies in Indonesia) - Meinura, Eka Dudy (Halaqa: Journal of Islamic Education, 2025)
Islamic Religious Education (PAI) teachers are not only responsible for the transfer of knowledge, but also for guiding and shaping the character of students in order to internalize Islamic values in both speech and behavior. Therefore, it is important to discuss professionalism, competence, issues, and policies related to PAI teachers. The purpose of this study is to analyze the Professionalism and Competence of Islamic Religious Education Teachers related to Issues and Policies in Indonesia. This research uses the literature review method. The literature review method is done by collecting theories that are relevant to the research issues discussed. Islamic Education teachers are expected to have competencies in accordance with Islamic teachings. A PAI teacher must be able to evaluate student learning outcomes to determine the level of success in the learning process of PAI subjects. In addition, they must be professional educators who are able to face and solve the problems faced by PAI teachers today.